Thermodynamic Analysis of Space Regenerative Orc (Srorc) System for Automotive Waste Heat Recovery. Issue 1 (1st February 2022) - Tong, D H; Kong, X H; Li, M; Liu, X; Huang, G L; Wang, X P
Abstract: In this paper, the space regenerative ORC (SRORC) system is proposed. In SRORC system, the superheated working fluid is divided into two parts after it works completely in the expander. The performance of SRORC system is studied, the performance of ORC system and SRORC system under different conditions are compared and analyzed. From the perspective of latent and sensible heat, the mechanism of using space regeneration to improve the performance of SRORC system is explored. The models of ORC system and SRORC system are built by Aspen plus software. R245fa is chosen as the working fluid because of its excellent performance. The simulation results show that compared with the evaporation temperature, the evaporation pressure has greater influence on the performance of SRORC system under B75 condition. Under C25, B50, A75, B75, and B100 conditions, compared with ORC system, the net output power of SRORC system is increased by 30.7%, 30.3%, 34.4%, 33.2% and 34%, the thermal efficiency is increased by 4.3%, 4.36%, 4.97%, 4.79% and 4.89%, the exergy efficiency is increased by 11.13%, 10.28%, 10.36%, 10.69% and 10.02%, the recovery efficiency of engine power is increased by 3.92%, 2.55%, 2.9%, 2.91% and 3.36%, respectively. The heat recovery rate of IHE-ORC system and SRORC system are 13.7kW and 24.8kW under B75 condition. In SRORC system, liquid working fluid can recover sensible and latent heat of superheated working fluid, and the latent heat accounts for most of the heat recovered.